Peningkatan Kepedulian Kebersihan Lingkungan di Kampung Wisata Yoboi Kabupaten Jayapura, Papua - Henderite L. Ohee; Lisye I. Zebua; Yokelin Tokoro; Ivana C. Lincani (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Our community service activities were focused on increasing the villagerâ€™s awareness on cleanliness. The program was conducted on February to November 2022, which consists of three main activities namely waste and waste management class, decorating rubbish bin and cleaning up trash. It was done by engaging children of Sunday School of Maranatha Church of the village. Waste and waste management class along with decorating rubbish bin was conducted on April 16, 2022. Meanwhile cleaning up trash in the village was conducted on April 23, 2022. The program was started with a pre test and closed with a post test. Children knowledge on waste and waste management was low (N-Gain = 0.11). Mostly, rubbish of the village contains of plastics. It is important to raise awareness and increase villagersâ€™ knowledge on the importance of maintaining a clean and beautiful spot in the village to attract more tourist to this destination.Keyword: Environmental education; Lake Sentani; Tourist destination; Yoboi.Â